Navigating Barriers and Building Strengths: A Case Study of Employment Success Among Blind Professional Women in Indonesia - Firmanda, Tommy (The Center for Disability Studies and Services Brawijaya University, 2025)
Employment remains a persistent challenge for individuals with visual impairments in Indonesia, often due to structural barriers, societal biases, and limited workplace accommodations. This initial qualitative case study explores how two visually impaired, millennial female professionals in Jakarta, Indonesia succeed in formal employment. The findings reveal five key themes that shape their experiences: (1) Institutional & Organizational Support, including accessible infrastructure and inclusive policies; (2) Personal Resilience & Self-Advocacy, highlighting determination and proactive communication; (3) Technical Proficiency & Continuous Learning, underlining the importance of assistive technology and ongoing skills development; (4) Peer Collaboration & Workplace Dynamics, emphasizing teamwork and mutual understanding; and (5) Emotional Impact & Identity Transformation, illustrating how adapting to unexpected challenges can redefine one’s professional self. The findings from the two case studies show that combining individual drive with supportive environments can remove barriers and foster career success for visually impaired individuals.